Pengaruh Ukuran Perusahaan, Reputasi Auditor, Opini Audit Terhadap Audit Delay: Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Sub Sektor Perusahaan Makanan dan Minuman Indonesia 2016-2021 - Fajar Ichwan; Fina Fitriyana (Yayasan Literasi Ilmiah Indonesia, 2023)
This study aims to determine: (1) The simultaneous effect of company size, auditor reputation, audit opinion and audit delay (2) The effect of company size on audit delay, (3) The effect of auditor reputation on audit delay, (4) The effect of audit opinion against audit delays. The influence of company size, auditor reputation, audit opinion and audit delay in manufacturing companies listed on the stock exchange in the Indonesian food and beverage companies sub-sector 2016-2021. This type of research is quantitative research using the document method. Samples were taken using purposive sampling technique. The sample totals 72 data from 12 manufacturing companies listed on the stock exchange for the Indonesian food and beverage company sub-sector 2016-2021. The data analysis technique used is descriptive statistics and panel data regression using Eviews 9.0. Based on the results showing that company size, auditor reputation, audit opinion simultaneously affect audit delay, company size has no effect on audit delay, auditor reputation has no effect on audit delay, audit opinion has an effect on audit delay. Keywords: company size, auditor reputation, audit opinion, audit delay